2023
DOI: 10.3389/fnhum.2023.1107858
|View full text |Cite
|
Sign up to set email alerts
|

Auditory P300 in individuals with high schizotypy: associations of schizotypal traits with amplitude and latency under different oddball conditions

Abstract: BackgroundThe aim of this study was to compare the characteristics of auditory P300 between non-clinical individuals with high and low schizotypal traits, and investigate the relationship between schizotypy and P300 under various oddball conditions.MethodsAn extreme-group design was adopted. After screening 1,519 young adults using the Schizotypal Personality Questionnaire (SPQ), sixty-three participants were chosen and divided into two groups (schizotypy group: 31 participants; control group: 32 participants)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…Of note, a few studies in the general population have also reported an association between reduced P300 amplitudes and schizotypal features (Davidson et al, 2018;Deng et al, 2023;Klein et al, 1999), which may reflect a genetic vulnerability for psychosis (e.g., Lenzenweger, 2018).…”
Section: Family Studies Of P300mentioning
confidence: 99%
“…Of note, a few studies in the general population have also reported an association between reduced P300 amplitudes and schizotypal features (Davidson et al, 2018;Deng et al, 2023;Klein et al, 1999), which may reflect a genetic vulnerability for psychosis (e.g., Lenzenweger, 2018).…”
Section: Family Studies Of P300mentioning
confidence: 99%